Endothelial Injury Biomarkers in Pediatric Lupus: Focus on Endocan as an Early Predictor of Vascular Dysfunction - Mona Hamed Gehad , Ezzat kamel Amin , Esraa Ashraf Mahmoud Ali , Rabab Mohamed Abdelhay , Weaam Ibrahim Ismail (Cuestiones de Fisioterapia, 2024)
Background: Pediatric-onset systemic lupus erythematosus (pSLE) is a chronic multisystem autoimmune disease characterized by heightened disease severity, cumulative organ damage, and increased long-term cardiovascular morbidity compared with adult-onset disease. Endothelial dysfunction represents a critical early event in the pathogenesis of premature atherosclerosis observed in children with lupus, often preceding overt clinical cardiovascular disease. Traditional cardiovascular risk assessment tools are insufficient in pediatric lupus, underscoring